Intelligent vehicle using embedded system - Aarti Meshram; Dipti Bichwe; Harshal Belsare (International Journal of Innovations in Engineering Research and Technology, 2021)
Unifying the Global Positioning system technology this article designs and realizes one kind of embeddedwireless system named intelligent vehicle control for critical remote location application usingmicrocontroller from the hardware and software. In terms of the hardware completed the design andconnection of embedded system, GPS module, obstacle testing module,different parameter monitoringsensor modules and the GSM module.